Conditions for the stability of an impulsive linear equation with pure delay - Ivanov, I. L.; Slyn'ko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish necessary and sufficient conditions for the stability of one class of impulsive linear differential equations with delay.